Mengenalkan Perubahan Warna dengan Pendekatan Interaktif di RA Al- Abror melalui Eksperimen Sains Pencampuran Warna-warna - Sriastuti, Widi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Through the use of experimental methods, this researcher seeks to increase children's focus. Kindergarten A RA Al-Abror. Class Action Research (PTK) is the research method used. The design developed by Kemmis and McTaggart was used in this research. Ten class A students served as study participants. The data collection approach is through observation with instruments. The aim of this research is to explore the effectiveness of an interactive approach in teaching the concept of color change to preschool children at RA Al-Abror. Research shows that children can improve their focus by experimenting with mixing colors. In this study, in the first indicator there were nine children who were in the BSH stage and one person was still in the MB stage, in the second indicator there were eight children who were in the BSH stage and two were still in the MB stage and in the third indicator there were eight children who were in the BSH stage. BSH and two people are still in the MB stage. before the experiment, the focus value was MB (Starting to Develop), but after the experiment, the value changed to BSH (Developing According to Expectations). This indicates a change in the child's focus as a result of the intervention carried out during the experiment. The results of this experiment are increased focus, knowing colors, mixing colors, changing colors, increasing thinking and creativity and being able to create good and creative ideas.